(Thia)calixarenephosphonic Acids as Potent Inhibitors of the Nucleic Acid Chaperone Activity of the HIV-1 Nucleocapsid Protein with a New Binding Mode and Multitarget Antiviral Activity - Humbert, Nicolas (AMER CHEMICAL SOC, 2023)
10.1021/acsinfecdis.9b00290